1989
DOI: 10.1071/pp9890321
|View full text |Cite
|
Sign up to set email alerts
|

Chilling Injury in Mature Leaves of Rice. I. Varietal Differences in the Effects of Chilling on Canopy Photosynthesis Under Simulated 'Dry Cold Dew Wind' Conditions Experienced in South-East China

Abstract: Canopy temperature and incident photosynthetically active radiation were measured in experimental rice plots in Guangzhou, South China, during conditions which approximated those of the 'dry cold dew wind', a chilling phenomenon which is responsible for substantial yield reduction in rice. These field conditions were then reproduced in controlled environment photosynthetic measurement chambers. Mature plants of five varieties of rice were arranged to simulate a canopy in these chambers which was then exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…For example, B. rugulosa contained more soluble saccharides and showed larger reduction in P N . This finding is supported by Huang et al (1989) who reported high content of soluble sugars and inhibition of photosynthesis at low temperature in rice leaves. On the other hand, high photosynthetic activity was associated with high proline content ( Fig.…”
Section: Recovery Of Plantssupporting
confidence: 83%
“…For example, B. rugulosa contained more soluble saccharides and showed larger reduction in P N . This finding is supported by Huang et al (1989) who reported high content of soluble sugars and inhibition of photosynthesis at low temperature in rice leaves. On the other hand, high photosynthetic activity was associated with high proline content ( Fig.…”
Section: Recovery Of Plantssupporting
confidence: 83%
“…Balance between sources and sinks can be upset when photosynthesis increases without a corresponding increase in import or when overall im port into sinks decreases without a comparable decrease in photosynthesis. In some cases photosynthesis may change (Huang et al, 1989b and references cited therein) while in other cases a change in partitioning among sinks may allow export to continue even though import into some sinks is inhibited (Fondy and Geiger, 1980). Experience tells us that adaptations exist which allow plants to restore and maintain the critical metabolic equilibrium between sources and sinks (Wardlaw, 1985).…”
Section: Responses Of Leaf Physiology To Source-sinkmentioning
confidence: 99%
“…Experience tells us that adaptations exist which allow plants to restore and maintain the critical metabolic equilibrium between sources and sinks (Wardlaw, 1985). For example, when source-sink balance is upset by hindered export, photosynthesis acclimation usually is seen only after a lag of a day or two (Mayoral et al, 1985;Plaut et al, 1987;Bagnall et al, 1988;Huang et al, 1989b). Physiological processes in leaves can respond rather quickly to some environmental changes; for instance, alterations in the pattern of the daily light regime, transient changes in irradiance caused by sun flecks or passing clouds (Pearcy, 1990), and onset of some forms of stress such as leaf water deficit.…”
Section: Responses Of Leaf Physiology To Source-sinkmentioning
confidence: 99%
“…Various short-term experiments have revealed that low temperatures can lead to considerable accumulations of carbohydrates in source leaves, which could potentially result in a feedback inhibition of photosynthesis (Azcon-Bieto, 1983;Paul et al, 1990;Stitt, 1991;Brüggemann et al, 1992 (Huang et al, 1989). Marked and sustained increases in carbohydrates were also found in cotton plants exposed for 4 d to low air temperatures (20 °C) during the light period (Königer and Winter, 1992 Winter and Königer, 1991) resulted in decreases in leaf turgor pressure.…”
Section: Cultivation Of Plantsmentioning
confidence: 99%
“…Little is known about the effects of different temperatures during the dark period on photosynthesis and growth of plants, since in most experiments temperatures were changed simultaneously during the light and dark period (eg Downton and Slatyer, 1972;Huang et al, 1989;Schleppi et al, 1990;Zollinger and Kells, 1991). Those experiments in which the temperature during the dark period was changed independently of the light period suggested that the night temperatures might have a significant impact on plant growth.…”
Section: Introductionmentioning
confidence: 99%